Chapel Royal St. James's Palace - Schnebbelie, Robert Blemmell; Wise, William (Tufts Archival Research Center, 2008)
Formerly part of the House for Female Lepers, established before the Norman Invasion. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 1.